Ageing study of different types of long-term pressure tested PE pipes by IR-microscopy. (20th March 2015) - Maria, Raquel; Rode, Karsten; Schuster, Tobias; Geertz, Guru; Malz, Frank; Sanoria, Abhishek; Oehler, Harald; Brüll, Robert; Wenzel, Mirko; Engelsing, Kurt; Bastian, Martin; Brendlé, Emmanuelle
Abstract: Although the lifetime of plastic pipes is commonly determined by hydrostatic pressure tests which measure the mechanical resistance, thermo-oxidative degradation plays an important role in practice. It is, therefore, an important question to monitor the elemental processes occurring during ageing of polymers, namely the loss of stabilising additives and the degradation of the polymer. The diffusion of the phenolic antioxidant AO-18, the processing stabiliser, and changes in polymer morphology during hydrostatic pressure testing, have been systematically studied for pipes made of PE 80 and PE 100 using infrared microscopy in a quantitative manner. For both materials a parabolic concentration profile of AO-18 develops over the pipe wall upon hydrostatic pressure testing. Under comparable conditions of testing the loss rate was larger for the PE 80 than for the PE 100. An annealing of the polymer occurs upon ageing with a similar increase in degree of crystallinity for both materials. However, the PE 100 has an overall higher level of crystallinity, and it may be speculated that this is one of the reasons for the slower loss of antioxidant. The results from IR-microscopy are in excellent agreement with analyses of samples taken over the pipe wall by oxidative induction time (OIT) and extraction → HPLC. The conversion of the phosphite additive PS-2 to the corresponding phosphate as a result of oxidation has been quantitatively assessed. The total content of phosphate and phosphite was found to be constant, and almost no extraction is seen before 5000 h. GPC analysis of samples taken proves that no significant reduction in average molar mass of the polymer takes place. Graphical abstract: Highlights: The long term durability of two types of PE pipes i.e., PE 80 and PE 100 has been investigated. A method has been developed to quantitatively determine the content of the phosphite additive in PE pipes. The degree of crystallinity and the content of stabilizing additives i.e., AO-18, HA(L)S-3 and PS-2 was profiled across the pipe wall after different times of ageing.